Assessment of Nerve Conduction Abnormalities in Peripheral Vascular Disease: A Clinical and Electrophysiological Correlation Using Nerve Conduction Studies and Ankle-Brachial Index in Patients with Chronic Ischemia - Dr. M. Arafath Natchiar; Dr. V. Chougule; Dr. B. Sankararaman, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Peripheral Vascular Disease (PVD) is a progressive circulatory disorder characterized by arterial narrowing, leading to reduced blood flow to the extremities. Chronic ischemia associated with PVD can cause significant neurological complications, including peripheral neuropathy. However, distinguishing between neuropathy caused by ischemia and other factors, such as diabetes, remains a challenge. Nerve conduction studies (NCS) serve as an objective tool to evaluate peripheral nerve function in PVD patients. This study aimed to assess nerve conduction abnormalities in PVD patients and correlate findings with disease severity. Methods: A prospective observational study was conducted on 40 patients diagnosed with PVD at Krishna Hospital, Karad, between May 2011 and May 2013. Patients were classified based on the Fountaine Staging System, and Ankle-Brachial Index (ABI) was used to determine the severity of arterial insufficiency. NCS was performed to evaluate motor and sensory nerve conduction velocities (NCV), compound motor action potential (CMAP), and sensory nerve action potential (SNAP). Patients with diabetes mellitus were excluded from the study to eliminate confounding factors. The relationship between PVD severity and nerve conduction abnormalities was analyzed statistically. Results: The study population comprised 24 males and 16 females, with a mean age of 59 years (range: 42-78 years). The distribution of patients according to Fountaine Staging revealed that 32.5% had ischemic rest pain (Stage III), and 7.5% presented with ulceration or gangrene (Stage IV). ABI values indicated that 67.5% of patients experienced claudication pain (ABI: 0.4–0.85), while 7.5% had rest pain (ABI < 0.4). NCS findings demonstrated significantly reduced motor and sensory NCV in advanced PVD stages, with mean values of 40.92 m/s (motor) and 44.88 m/s (sensory). Furthermore, CMAP and SNAP amplitudes were markedly decreased in patients with severe PVD, suggesting ischemic nerve damage. Conclusion: This study highlights a strong correlation between PVD severity and nerve conduction abnormalities, indicating that ischemic neuropathy plays a critical role in disease progression. Sensory nerve dysfunction was more pronounced than motor involvement, aligning with findings from previous studies. Early detection of nerve conduction deficits in PVD patients may facilitate timely interventions to prevent further neurological complications. Incorporating routine NCS assessments alongside vascular evaluations could improve diagnostic accuracy and patient outcomes in PVD management. Further studies with larger cohorts are recommended to validate these findings and explore potential therapeutic strategies.